Novel approaches for the treatment of methicillin-resistant Staphylococcus aureus: Using nanoparticles to overcome multidrug resistance. Issue 1 (January 2021) - Vanamala, Kushal; Tatiparti, Katyayani; Bhise, Ketki; Sau, Samaresh; Scheetz, Marc H.; Rybak, Michael J.; Andes, David; Iyer, Arun K.
Highlights: Superbugs such as MRSA are highly prevalent infections with high mortality rates. Biofilms and antibiotic resistance impede effective treatment of MRSA. Conventional therapies are ineffective because of multiple resistance mechanisms in MRSA. Targeted nanoparticles that can overcome biofilms and drug resistance hold great promise for successful MRSA treatment. Abstract : Methicillin-resistant Staphylococcus aureus (MRSA) causes serious infections in both community and hospital settings, with high mortality rates. Treatment of MRSA infections is challenging because of the rapidly evolving resistance mechanisms combined with the protective biofilms of S. aureus . Together, these characteristic resistance mechanisms continue to render conventional treatment modalities ineffective. The use of nanoformulations with unique modes of transport across bacterial membranes could be a useful strategy for disease-specific delivery. In this review, we summarize treatment approaches for MRSA, including novel techniques in nanoparticulate designing for better therapeutic outcomes; and facilitate an understanding that nanoparticulate delivery systems could be a robust approach in the successful treatment of MRSA. Teaser: For the ever-changing resistance to infections, nanoparticle-mediated drug delivery holds great promise for achieving better treatment outcomes.